A Study On The Audit Expectation Gap In Malaysia - Fadzly Mohamed Nazri, (2003)
This study focuses on the expectations of auditors and users of financial statements in malaysia towards statutory audit. The main objectives are to measure the level and nature of the audit expectation gap in Malaysia and to explore the potential of a reading material as an alternative means of audit education . In achieving these objectives, two separate research methods were employed. The first objective was achieved using the methodology adopted from Schelluch(1996) and Best et al.(2001)